Study of Electrical Constraints within Cavities in High Voltage Cables - MEDOUKALI , H.; GUIBADJ, M.; ZEGNINI, B. (International Journal of Computational and Experimental Science and Engineering, 2015)
This paper studies the electrical constraints within an XLPE insulated cable containing micro-cavities. The purpose of this work is to determine by simulation the distortions caused by micro-cavities on the electric field distribution in the insulating layer of cable. The computation method used to determine the electric field is based on numerical resolution of Laplace equation using the finite element method. The threshold of partial discharges ignition in gaseous cavities contained in XLPE insulation of 30 kV cable is studied. The computation of the critical field by approached formula of Paschen permits us to elucidate the harmfulness caused by a cavity according to its size and its position.